Omsk Hydroelectric Power Plant Project in Economic History of Region in 1930s—1980s. - M. S. Mostovenko (Научный диалог, 2024)
The article is dedicated to the unrealized project of the Omsk Hydroelectric Power Station, developed in the 1930s, then postponed and subsequently reintroduced for discussion in the 1980s. The sources used for this research include materials from the Historical Archive of the Omsk Region and the Russian State Archive of Economy. Both domestic and foreign historiography on the economic development of Western Siberia do not mention this project, hence this article aims to fill this historiographical gap. It is demonstrated that the project was considered by regional authorities solely as an agricultural facility, which would have allowed for the use of the reservoir for irrigation in the southern districts of the region and improvement of navigational conditions around the city of Omsk. Emphasis is placed on the fact that its implementation could have boosted the industrial development of the Omsk Region. The abandonment of the project in the 1930s largely determined the subsequent development of the region, particularly from an ecological perspective. To meet the energy needs of the city and the region, construction of thermal power plants began, fueled by Ekibastuz coal, which contains a large amount of ash. This, in turn, led to serious air pollution in the Omsk region, which continues to persist to this day.